2014
DOI: 10.1186/1471-2164-15-395
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different extraction techniques to profile microRNAs from human sera and peripheral blood mononuclear cells

Abstract: BackgroundmicroRNAs (miRNAs) play crucial roles in major biological processes and their deregulations are often associated with human malignancies. As such, they represent appealing candidates as targets of innovative therapies. Another interesting aspect of their biology is that they are present in various biological fluids where, advantageously, they appear to be very stable. A plethora of studies have now reported their potential as biomarkers that can be used in diagnosis, prognosis and/or theranostic issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 29 publications
(33 reference statements)
1
41
1
Order By: Relevance
“…This issue has already been postulated by Monleau et al . Since we were able to gain the best results with the method that was optimized for isolation of bulk tRNA, we speculate that the mechanism of tRNA‐derived fragments loss during the isolation procedure is related to specific characteristics of tRNA molecules, including sequence, structure or high molecular interaction partners.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has already been postulated by Monleau et al . Since we were able to gain the best results with the method that was optimized for isolation of bulk tRNA, we speculate that the mechanism of tRNA‐derived fragments loss during the isolation procedure is related to specific characteristics of tRNA molecules, including sequence, structure or high molecular interaction partners.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the miRNeasy kit presents the highest theoretical concentration factor, our data showed that the NucleoSpin ® miRNA plasma kit provides higher endogenous miRNA concentrations and performs as well as the others, when reproducibility is assessed. Using high‐throughput PCR arrays, the NucleoSpin ® miRNA plasma kit has been recently described as more efficient than other kits (miRNeasy and Norgen) to isolate serum miRNAs (Monleau et al., 2014) and as presenting the least extraction bias (Tan et al., 2015) in agreement with our individual PCR assays. We provided additional data showing its higher performance on both serum and plasma miRNA isolation using individual absolute RT‐qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tackled this point, focusing on methods for miRNA extraction (Monleau et al 2014;Li and Kowdley 2012;Podolska et al 2011); however, similar considerations could also be true in analyzing sdRNAs.…”
Section: Introductionmentioning
confidence: 99%